Teach [IT]: Turning the Classroom into a Research Laboratory via Interactive E-Learning Tools - Burckhardt, Philipp; Chouldechova, Alex; Nugent, Rebecca (International Conference on Teaching Statistics, 2018)
This paper introduces ISLE (Interactive Statistics Learning Environment), an authoring framework for building interactive statistics lessons that supplement classroom instruction. Using a case study of two university courses at Carnegie Mellon University (“R Programming for Analytics” for graduate students,“Reasoning with Data” for undergraduates) we show how ISLE helps to blend off-line and on-line instruction. Features that facilitate ISLE’s blended learning approach include 1) a hint, assessment, and feedback system 2), on-the-fly data collection from students eg through surveys, and 3) real-time peer-to-peer communication and monitoring of student actions. ISLE also allows collection of all user interactions, including mouse clicks and text inputs along with their associated timestamps. It is our hope that this will give instructors new insights into patterns of student learning.